(untitled) (Research, Society and Development, 2023)
This research aims to improve students’ pronunciation of the -S ending sound in a group of twenty-one EFL learners from a private high school on the Ecuadorian coast where the pronunciation of the -s ending appears weak on them. By using PRAAT computer software and exploring whether, after using it, their pronunciation had improved; To answer this question, we present to students the specific grammar aspect of /z/ /iz/ /s/ English pronunciation, recorded sounds with complete sentences, verbs and nouns from a native English speaker is used to help students to analyze their pronunciation as the native speaker does by using this software. The final results demonstrated that some learners improved their pronunciation of the -S ending sounds, yet others did not; students concerned about their English proficiency improved compared to the ones with low proficiency levels. The study suggests using technological tools to teach and learn pronunciation, as some students do not like to learn a second language. Teachers must apply their curriculum to teach pronunciation with the help of technological tools.